VEGETATIVE PHASE CHARACTERIZATION OF BLACK RICE VARIETIES FROM WEST BORNEO GROWN IN RED-YELLOW PODSOLIC SOIL - Pangaribuan, Franky; Palupi, Tantri; Zulfita, Dwi (Jurnal Sains Pertanian Equator, 2017)
Black rice is a type of rice species known to have anthocyanin contents beneficial to human health. West Borneo have several potential black rice varieties used as genetic resources to create a new black rice variety in plant breeding program. This research is aimed to determine of characters"™ information and to find out the genetic relationship among black rice varieties from West Borneo. The research was conducted at experimental garden of Agriculture Faculty, University of Tanjungpura, Pontianak. The experiment is arranged according to Completely Randomized Design (CRD) consisting of four levels i.e., A=Nanga Taman black rice, B=Sanggau black rice, C=Senakin black rice, D=Ensalang black rice. Each treatment consists of six replications and each replication consists of 3 samples. This research obtains 16 characters of vegetative phase of Nanga Taman black rice, Sanggau black rice, Senakin black rice, and Ensalang black rice i.e., leaf blade length, leaf blade width, leaf blade pubescence, leaf blade attitude, collar colour, leaf sheath colour, ligule shape, ligule length, ligule colour, flag leaf attitude, flag leaf length, flag leaf width, leaf blade colour, auricle colour, childbearing, and culm length at vegetative phase. Nanga Taman black rice and Ensalang black rice has the fartest genetic relationship with 53,8% similarity level, at the same time Senakin black rice and Ensalang black rice has the closest genetic relationship with 99,3% similarity level.